Synthesis and Characterization of Ceria-based Electrolyte for Intermediate Temperature Solid Oxide Fuel Cell - Kaur, Taranveer (My University, 2024)
Solid oxide fuel cells (SOFC) are environment-friendly energy conversion devices in which chemical energy transforms directly into electrical energy. These devices are highly efficient and can work with various fuels. In this process, apart from electricity, SOFC produces water steam as a by-product that can be used to co-generate electricity. Further, they can also be used in electrolysis mode to generate hydrogen and oxygen gases. Even though SOFCs have many advantages, the high operating temperature (i.e., 800-1000 °C) is a crucial bottleneck in realizing its full potential. High operating temperature poses several problems regarding the choice of materials, particularly for interconnects and glass seals. It also leads to faster interfacial reactions, material degradation, and increased operational and fabrication costs. These complexities can be overcome by reducing the operating temperature to less than 800 °C. Electrolytes are vital components in deciding the operating temperature of SOFC. The conventional SOFC uses yttria-stabilized zirconia (YSZ) as an electrolyte, which operates between 800-1000 °C. High ionic conductivity, chemical and thermal stability, as well as a dense structure, are some of the essential requirements for an electrolyte. Doped ceria is a better choice for electrolytes at intermediate temperature (500-800 °C) due to its high conductivity and better compatibility with other cell components in this temperature range. The present thesis investigates Gd and Sr doped and co-doped ceria samples with a focus on solid oxide fuel cell development. The samples are synthesized using an ultrasound-assisted sol-gel auto-combustion method. The samples were characterized for their structural, thermal, and electrical properties. The selected electrolytes are sandwiched between the anode and cathode and tested in real SOFC conditions. The thesis is divided into six chapters, with a list of references provided at the end of the thesis. Chapter 1 introduces fuel cells and SOFCs with a brief account of the different categories of fuel cells. The fuel cells are categorized depending on the electrolytes used in them. The properties of various SOFC components, such as anode, cathode, electrolyte, interconnects, and sealants, are also discussed in this chapter. The different designs and configurations of the SOFC are also mentioned in this chapter, emphasizing the planar design of SOFC. Chapter 2 focuses on the literature related to ceria-based electrolytes. The ceria-based electrolytes show good conductivity at temperatures less than 800 °C. These electrolytes can help lower the operating temperature of the SOFCs. This chapter reviews the role of dopants in producing oxygen vacancies in the ceria lattice and their effect on the conductivity of these electrolytes. The different dopants and their concentration, co-dopants, and synthesis techniques are some of the factors that influence the performance of ceria-based electrolytes are also discussed. Based on the above literature, the motivation of the present study is provided, followed by the objectives of the present research work. The detailed synthesis methods of Gd-doped, Sr-doped, and Gd-Sr co-doped ceria samples are given in Chapter 3. The samples are characterized using different techniques namely thermogravimetric analysis (TGA) for thermal characterization, X-ray diffraction (XRD) analysis for crystal structure, Raman studies for local structural analysis and vacancy ordering, scanning electron microscopy (SEM) for microstructural and surface analysis. The conductivity and activation energy of the sintered samples have been determined using impedance spectroscopy. Further, the prepared cells are characterized in real SOFC conditions. The technical details of these methods are discussed in this chapter. Chapter 4 discusses the individual doping of Gd and Sr and the co-doping effect of both cations on the different structural, microstructural, and electrical properties. Doping of Gd and Sr in the ceria introduces oxygen vacancies in the lattice. XRD patterns confirm the cubic fluorite structure of the doped and co-doped samples. Although 30 % Gd-doped ceria sample and 10 % Sr-doped ceria sample showed the existence of secondary phase. The existence of secondary phase is confirmed by the trends in the lattice parameter and Raman spectra. Raman spectra also confirm the existence of intrinsic and extrinsic oxygen vacancies produced by the dopants (Gd 3+ and Sr 2+ ) and the conversion of Ce 4+ to Ce 3+ . The XPS data has been used to verify the existence of the Ce 4+ and Ce 3+ ions in the lattice. The microstructural studies showed a highly dense structure, showing partial liquid phase sintering in Sr-doped and Gd-Sr co-doped samples. The conductivity analysis showed increased conductivity in doped and co-doped samples compared to the undoped samples. The 10 % Gd-doped ceria sample showed the highest conductivity of 1.67 × 10 -2 Scm -1 , followed by 10 % Gd and 2.5 % Sr co-doped ceria sample, which showed 1.20 × 10 -2Scm -1 at 600 °C. In chapter 5, the optimization of the anode for the tape-casting process and the electrolyte for the spray-coating process is discussed. The anode-supported cells are made by tape casting the anode and spray coating the electrolyte. The anode and electrolyte are co-sintered together at 1450 °C for 4 h. The cathode is then painted on top of electrolyte and sintered at 1000 °C for 2 h, forming the complete cell. The fractured surface images of the cells show highly dense electrolytes sandwiched between two porous electrodes. The complete cell is studied in real SOFC conditions using hydrogen (3 % H 2 O) as fuel on the anode and ambient air on the cathode side. A highest power density of 112.7 mWcm -2 has been achieved for 10 % Gd and 2.5 % Sr-doped ceria samples. Chapter 6 concludes the results discussed in the previous chapters on Gd-doped ceria, Sr- doped ceria, and Gd-Sr co-doped ceria. The doped ceria electrolyte with cubic fluorite structure is formed. The solid solubility limit of Gd, Sr, and Gd-Sr co-doped in ceria is ~20 %, ~7.5 %, and 5.0 %, respectively. The highest conductivity is observed for 10 % Gd doped CeO 2 (1.67 × 10 -2 Scm -1 at 600 °C), followed by 10 % Gd-2.5 % Sr doped ceria and then 10 % Gd and 5.0 % Sr doped ceria. Based on optimization and conductivity, the four samples, CG1, CS3, CG1S1, and CG1S2, are fabricated and tested in real SOFC conditions. In these series, Ce 0.875 Gd 0.1 Sr 0.025 O 1.925 shows the best results regarding phase stability, microstructure, conductivity, and power density. This implies that Ce 0.875 Gd 0.1 Sr 0.025 O 1.925 can be a potential candidate as an electrolyte for intermediate-temperature SOFCs. The chapter concludes with a discussion of future perspectives and suggestions for the study.
Keywords: Solid Oxide Fuel Cell; Electrolyte; Ionic Conductivity; Cerium Oxide; Ceramics